Wage differentials in domestic work: The impact of contractual arrangements - Suleman, F. (2015)
The regulation of employment relationships dates back to the process of industrialization where workers had dangerous and injurious working conditions. However, pervasive poor conditions, together with a wide range of contractual arrangements, demand additional efforts from national and international institutions. The Employment Relationship Recommendation (Recommendation 198) (ILO 2006) and the Decent Work Agenda, illustrate the International Labor Organization’s (ILO 2002) efforts to guarantee protection of workers’ rights in labor laws and other regulations, including collective agreements. These initiatives also attempt to bring more hidden types of employment relationships under the protection of the law. However, the assessment of the impact of such initiatives is still missing in the literature. Our article attempts to fill this gap and to offer empirical evidence on the role of regulations in the labor market of domestic workers (...)